Soybean insect diversity in different cropping combinations - Cervancia, Cleofas R. (1985)
The cropping patterns evaluated were soybean monoculture, soybean-mungbean, soybean-peanut soybean-tomato, soybean-corn and soybean-peanut-tomato-corn intercrops The indices of diversity of the total samples from the different cropping patterns were calculated. For both seasons, soybean-corn and soybean-mungbean-peanut-tomato-corn intercrops had the highest diversity indices. Lamprosema indicata was the most dominant species in both dry and wet season.
Includes bibliographical references (page 92) and index.
Keywords: Agriculture; Soybean insect diversity; Soybeans -- Intercopping